Sex-specific Association between Psychopathic Traits and Electrodermal Reactivity in Children - Isen, Joshua (2010)
This study investigated the relationship of skin conductance response (SCR) to a child psychopathy measure. Blunted electrodermal activity is a theoretically important characteristic of psychopathy, but has not been fully explored in preadolescents or females. We tested the hypothesis that reduced SCR magnitude is associated with psychopathic-like traits in boys and girls. Participants were drawn from an ethnically diverse community sample of 9-10 year old twins. Given the fact that members of each twin pair were rated by the same individual (i.e., their caregiver) on the Child Psychopathy Scale, we examined individual differences at the within-family level. Skin conductance data were collected during a passive auditory task consisting of 75-dB tones as well as miscellaneous sounds (e.g., baby cries, bird noises, and speech-like stimuli). Reduced SCR magnitude (hyporeactivity) was only characteristic of boys with higher psychopathy scores. More specifically, electrodermal hyporeactivity was linked to the interpersonal facet of psychopathy, suggesting that it is a biological marker of a manipulative and deceitful orientation in males. No association was found between SCRs and psychopathic traits in girls, indicating the importance of sex specific etiologies of psychopathy in childhood.